FROM MAID TO MOTHER: TRANSFORMING FACILITIES, STAFF TRAINING, AND CAREGIVER DIGNITY IN AN INSTITUTIONAL FACILITY FOR YOUNG CHILDREN IN NEPAL. Issue 2 (22nd January 2014) - Wright, Amy Conley; Lamsal, Dhirendra; Ksetree, Mukunda; Sharma, Aalok; Jaffe, Kenneth; McCall, Robert B.; Groark, Christina J.; Rygaard, Niels P.
ABSTRACT This article provides a case study of a project to improve the health, safety, and development of children birth to 6 years old in a large orphanage in Nepal. Two interventions were conducted: improvement of physical infrastructure and training, mentoring, and support for caregiving staff. As a result of these interventions, positive outcomes in terms of children's health and development have been observed, including reduction of communicable diseases and increased social interactions with caregivers. As part of the new trainining initiative, the caregivers began to meet regularly to share their ideas and experiences, and came to realize their vital role in the holistic development of the children in their care. One important change was a greater sense of dignity for the caregivers. The caregivers were formerly called Maids (Aaya), but asked to be called Mothers (Aama). The project also faced challenges, including communication barriers related to organizational structure.